A German officer in occupied Paris : the war journals, 1941-1945 : including "Notes from the Caucasus" and "Kirchhorst diaries" - Jünger, Ernst 1895-1998 (Columbia University Press, 2019)
First Paris journal -- Notes from the Caucasus -- Second Paris journal -- Kirchhorst diaries.